Peran Job Crafting pada Work Engagement Guru Yayasan “X” di Kota Bandung - Jacqueline Tjandraningtyas; Meta Dwijayanthy; Michelle Ratna Salim (Humanitas (Jurnal Psikologi), 2025)
Fulfilling job demands and work responsibilities requires various resources, both from the teachers themselves and from the organization. Effective management of job resources can help teachers meet job demands. The JD-R (Job Demands-Resources) model is aimed at increasing teachers' work engagement with their profession. This study seeks to examine the role of job crafting in relation to work engagement among teachers. The theories used are the work engagement theory by Bakker, et al. (2008), and the job crafting theory by Tims and Bakker (2010, 2012). The study focuses on teachers who have worked for at least one year at Foundation "X". The data analysis technique used in this research is hierarchical regression analysis, observing the role of job crafting on work engagement, with the addition of demographic data of the teachers. The results show that job crafting affects work engagement among teachers. The correlation value (R) is 0.40, and the coefficient of determination (R square) is 0.17. This means that the job crafting variable (independent variable) has an influence of 17% on the work engagement variable (dependent variable). Demographic data, including age, number of children, spouse's employment status, and education level, strengthen the role of job crafting in relation to work engagement. The results of this study can serve as a basis for enhancing work engagement through the improvement of job crafting. Schools can strive to provide teachers with the freedom to explore innovations and be creative in the teaching process. The recommendations from this study are addressed to the research subjects to enhance their job crafting and make use of their demographic characteristics in order to remain engaged with their work. For schools, it is necessary to improve job crafting and to implement teacher development programs that take into account demographic data, which can strengthen the role of job crafting in promoting work engagement.